Huangqi Jianzhong decoction improves gastric intestinal metaplasia in rats by regulating the gut‒thyroid axis - Xiao, Ling; Cheng, Yu-qin; Ma, Wen-shuo; Zhu, Wen-fei; Wu, Jian-ping; Meng, Yu-fen; Shi, Li-yun; Zhang, Wei; Chen, Lei; Cheng, Chun; Zhang, Jun-feng (Phytomedicine (Stuttgart), 2024)
•GIM rats exhibited gastro-thyroid comorbidities with cold-intolerant. HQJZ treatment restored low-temperature-tropism behavior, enriching fecal butyrate-producing bacteria, and improved thyroid tissue lesions.•In vivo and in vitro experiments proved that butyrate improved thyroid tissue lesions, enhanced the expression of the thyroid TG, TPO, and TSHR genes, promoted T3 and T4 synthesis and secretion.•The gut microbiota-thyroid axis plays a key role in HQJZ improving the low-energy metabolism of GIM rats, which provides solid evidences for the clinical application of HQJZ in cold-intolerant PLGC patients. Gastric intestinal metaplasia (GIM) is a crucial stage in the progression of gastric cancer. Huangqi Jianzhong decoction (HQJZ) has emerged as a leading therapeutic strategy for treating GIM patients with cold intolerance in traditional Chinese medicine clinics, but the detailed mechanism remains poorly understood. The present study aimed to elucidate the molecular mechanism by which HQJZ alleviates GIM in a rat model on the basis of the gut microbiota‒thyroid axis. A GIM rat model was established by administering cold salicylic acid and sodium deoxycholate (SDC) for 12 weeks, followed by gavage treatment with HQJZ for an additional four weeks. Lianpu Yin (LPY) was used as a comparison formula. The cold tolerance characteristics of GIM rats were evaluated using cold tolerance and temperature‒tropism experiment experiments. Thyroid pathological changes were evaluated with HE staining, and thyroid function was measured via quantification of T3 and T4 levels with ELISA. The gut microbiota was analyzed using 16S rRNA gene sequencing, and fecal butyric acid and serum metabolites were quantified utilizing metabolomics. The key molecular mechanism was verified in the Nthy-ori 3–1 cell model. HQJZ, but not LPY, significantly improved gastric mucosa and thyroid tissue lesions in GIM rats, increased the serum levels of the thyroid hormones T3 and T4, and enhanced cold tolerance. HQJZ treatment promoted the enrichment of fecal butyrate-producing bacteria, specifically the bacteria Allobaculum and Bifidobacterium, resulting in a marked increase in fecal butyric acid concentrations. HQJZ treatment significantly diminished the levels of mitochondrial damage-related serum metabolites, including p-cresol sulfate and indoxyl sulfate. Mechanistically, in vivo investigations further demonstrated that butyric acid not only improved thyroid tissue lesions but also restored the fecal microbiota structure, as well as low-temperature tropism, in GIM rats. Furthermore, butyrate diminished the mitochondrial damage induced by SDC in these cells, as evidenced by decreased reactive oxygen species levels and increased ATP production and mitochondrial membrane potential. Importantly, in vitro studies revealed that butyrate protected against SDC-induced injury in Nthy-ori 3–1 cells through the upregulation of TG, TPO, and TSHR expression. HQJZ promotes cold tolerance and improves thyroid function in GIM rats by enriching gut butyrate-producing bacteria. [Display omitted]